The Relationships of Temperature and Humidity in AirConditioned Room to the Occurrences of Sick Building Syndrome - Siti Hanifah1 , Zikri Fathur Rahman2 , Abdul Rohim Tualeka3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
High rates of Sick Building Syndrome in other countries where pollution levels are far lower than Indonesia,it is suspected that Sick Building Syndrome in Indonesia is already worrying and that pollution levels are veryhigh. This syndrome can cause respiratory infections and can worsen people with asthma and allergies due todirty air. The main objective of this study is to analyze the relationship of temperature and humidity in airconditioned rooms to the emergence of Sick Building Syndrome in UPT PSMB-LT Surabaya. This researchis a descriptive study using an observational and approach cross-sectional. The population in this studywere all employees who worked at UPT PSMB-LT Surabaya, as many as 35 people, using Non-ProbabilitySampling namely techniques, total sampling. Data collection is done by interview and observation. Datawill be processed and presented in the form of frequency tabulation and described using a contingencycoefficient test. The results of this study indicate that the measured air temperature meets the standardsexcept for the physics laboratory room and the air humidity measured mostly does not meet the standardsexcept the leadership room, treasurer room, quality assurance room, physics laboratory room and cationroom. Symptoms of Sick Building Syndrome most commonly complain of symptoms on the skin. There is amoderate relationship between the incidence of Sick Building Syndrome and age. Suggestions for companiesare to pay attention to the temperature of the air inside and outside the room as well as the humidity of theair, SBS complaints need to be aware of early on, use a lotion before entering an air-conditioned room.